Timing theoretical-practical test method in Anatomy subject. Ten years of a pedagogical novelty. - Armando Hidalgo de Paz (Medisur)
Some years ago, a national resolution established a final theoretico-practical exam. In order to carry out this task avoiding the inconveniences of traditional exams , the method the timed theoretico-practical exam was designed and put into practice with the objective to examine all the theoretic and practical aspects without the direct intervention of the professors and to guarantee that all the students had the same time to answer their questions.. To develop it the members of the discipline had to carry out four tasks: Organisation, Setting up, Development and Assessment. This method designed and used satisfactorily by the professors of Anatomy has been applied for a 10 year-period and has been generalised to other medical subjects not only at the Cienfuegos Medical College but also in other medical Colleges of the country.